Mekanisme Pembatalan Penjualan Instishna dalam Islam - Sari, Reonika Puspita (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
This study aims to determine the system of istishna sale and purchase cancellation which is justified according to Islamic law. This is library research which is carried out by collecting data which is then analyzed to solve a problem that is focused on a critical and in-depth study of the relevant library materials. According to the results of the study, the cancellation of the istishna sale and purchase contract is allowed unless it is caused by things justified by syara', for instance, a defect in the object of the contract or does not meet one of the pillars or conditions of the contract. This is by the MUI fatwa No: 06/DSN-MUI/IV/2000. In addition, the cancellation of the contract must be approved by both parties without harming either party. This is confirmed in the Qur'an Surah an-Nisa verse 29.